Nanoencapsulação de ftalocianina de zinco para o uso em terapia fotodinâmica - Souza, Thiane Deprá de (2015)
The present work aims to investigate the influence of nanoencapsulation of zinc phthalocyanine photosensitizer (ZnPc) in polymeric nanoparticles for use in photodynamic therapy (PDT). Three formulations of ZnPc loaded nanocapsules (ZnPc/NCs), conventional and lipid core, constituted by polymers chitosan (NCA), poly-ε-caprolactone (NCB), and poly-ε-caprolactone coated with chitosan (NCC) were prepared by the interfacial deposition of preformed polymer method. The physicochemical characterization of ZnPc/NCs was performed (hydrodynamic radius, polydispersity index, zeta potential, pH, encapsulation efficiency, morphology and stability indicative evaluation at different temperatures over time). Photophysical (ZnPc aggregation) and photochemical studies (photodegradation of 1.3-diphenylisobenzofuran, DPBF, of ZnPc, and calculation of singlet oxygen quantum yield, Δ) were carried out and an evaluation the in vitro release kinetics study was also be done. The formulations presented physicochemical characteristics suitable to our expectations, with particle size in the nanometer scale (119 nm ± 3.86, 95 nm ± 0.82 and 83 nm ± 0.54 to NCA, NCB and NCC, respectively), index polydispersity lower than 0.24. Regarding the zeta potential, the nanocapsules showed positive and moderately high value for NCA and NCC (+34 mV ± 3.65 and +22 mV ± 0.46, respectively) and a negative one for NCB (-13 mV ± 0.80) and all formulations showed high encapsulation efficiency (greater than 99%). The ZnPc/NCs showed spherical shape and were stable during the storage time (90 days) at temperatures of 25 °C and 37 °C. Regarding the photophysical and photochemical studies, the free ZnPc (unencapsulated) did not suffer aggregation in the concentrations and solvents studied, and the ZnPc/NCs efficiency for the production of 1O2 was been confirmed by the high values found for Δ (0.61 ± 0.13, 0 36 ± 0.04, 0.41 ± 0.02 for NCA, NCB and NCC, respectively). In the time scale usually used in PDT (150 s) the photosensitizer shows photostability and only a small photodegradation was been observed when a high dose of light was applied. The release kinetics study of ZnPc loaded nanocapsules showed controlled release and no burst effect. The release profile follows the Higuchi's kinetic model for nanocapsules indicating that the process is controlled by diffusion, whereas the release depends on the system composition and increases in the order: NCC <NCB <NCA. Based on the results obtained in this work, the conventional and lipid core nanocapsules containing ZnPc are promising delivery systems for use in PDT.